Uncovering the Mast Cell Response to Mycobacterium tuberculosis - Torres-Atencio, Ivonne; Campble, Ariadne; Goodridge, Amador; Martin, Margarita (Frontiers in Immunology, 2022)
The immunologic mechanisms that contribute to the response to Mycobacterium tuberculosis infection still represent a challenge in the clinical management and scientific understanding of tuberculosis disease. In this scenario, the role of the different cells involved in the host response, either in terms of innate or adaptive immunity, remains key for defeating this disease. Among this coordinated cell response, mast cells remain key for defeating tuberculosis infection and disease. Together with its effector’s molecules, membrane receptors as well as its anatomical locations, mast cells play a crucial role in the establishment and perpetuation of the inflammatory response that leads to the generation of the granuloma in the case of tuberculosis. This review highlights the current evidences that support the notion of mast cells as key link to reinforce the advancements in tuberculosis diagnosis, progression, and therapeutic targets. Special focus on mast cells capacity for the modulation of the inflammatory response among patients suffering multidrug resistant tuberculosis or in co-infections such as current COVID-19 pandemic.